H.264 AVC를 위한 내부 예측 - Teshome Mikiyas (The Graduate School, Ajou University, 2010)
Acknowledgment I do not have enough words to thank Professor Kim Dong-Yoon. You are the main reason for whatever I achieved so far. Thank you so much for all the trust, fatherly advice and encouragement; thank you so much for the thoughtfulness and kindness you showed me. I will never forget what you did. I would also like to sincerely thank Professor Wee Yung-chul for offering me such a wonderful chance to work with you. It was a great privilege to have been advised and guided by a brilliant professor like yourself. You assisted and taught me a lot and I so much appreciate your brains. I also thank Professor Shin Hyun-Joon for always telling me that I can do it, keeping my spirits high. For sharing your experience and being patient with whoever I was in those moments I worked with you. I appreciate your understanding, the ideas you generate and superb comments you give. Thank you so much Professor Lee Yun-Jin, for being so kind and for quenching my thirst of the basic concepts in computer graphics. I cherished your class and the knowledge I acquired helped me to answer some basic questions when doing this research. My acknowledgement will never be complete with out mentioning the accompany I had from Legesse Zerubabel. You were always there whenever I needed some one to talk to, sharing my burdens and worries. I thank Jonghyuk Kim and all the other members of the visual computing lab for being so wonderful to me and lending a hand whenever I needed one. I would also like to thank Mee-yeon Woo for taking care of my issues with the department. You were so caring and helpful. Special thanks to Chan, Anatolly and all my Ethiopian and Korean friends for making my stay at Ajou so much fun and easy. Finally, I would not have reached here if it was not for the life transforming scholarship I got from the Institute of Information Technology Advancement and Ajou University. Thank you. Praise be to God!
학위논문(석사)--아주대학교 일반대학원 :컴퓨터공학과,2010. 2
Keywords: H.264; INTRA PREDICTION; 인코더 매개변수